Earthquake Prediction and Seismicity Patterns 1979
DOI: 10.1007/978-3-0348-6430-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Gaps and Plate Tectonics: Seismic Potential for Major Boundaries

Abstract: -The theory of plate tectonics provides a basic framework for evaluating the potential for future great earthquakes to occur along major plate boundaries. Along most of the transform and convergent plate boundaries considered in this paper, the majority of seismic slip occurs during large earthquakes, i.e., those of magnitude 7 or greater. The concepts that rupture zones, as delineated by aftershocks, tend to abut rather than overlap, and large events occur in regions with histories of both long-and short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
203
3
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(211 citation statements)
references
References 67 publications
3
203
3
2
Order By: Relevance
“…Kelleher and Savino (1975) demonstrated that gaps in seismicity for great earthquakes are also gaps for smaller magnitude activity and such gaps commonly persist until the time of the mainshock. A very comprehensive review can be found in McCann et al (1980). Usually these seismic gaps refer to a spatial gap of seismic activity, particularly of large earthquakes.…”
Section: Foreshocksmentioning
confidence: 99%
“…Kelleher and Savino (1975) demonstrated that gaps in seismicity for great earthquakes are also gaps for smaller magnitude activity and such gaps commonly persist until the time of the mainshock. A very comprehensive review can be found in McCann et al (1980). Usually these seismic gaps refer to a spatial gap of seismic activity, particularly of large earthquakes.…”
Section: Foreshocksmentioning
confidence: 99%
“…For more references please see Rong et al (2003). Perhaps the most comprehensive studies covering the whole of the circum-Pacific plate boundaries are those of McCann et al (1979) and Nishenko (1991). McCann et al (1979) provided the earthquake potential on the basis of time elapsed since the last large event, assuming that characteristic earthquakes occur quasi-periodically and that a mean recurrence time and its standard deviation can be estimated from the historical record of such events.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most comprehensive studies covering the whole of the circum-Pacific plate boundaries are those of McCann et al (1979) and Nishenko (1991). McCann et al (1979) provided the earthquake potential on the basis of time elapsed since the last large event, assuming that characteristic earthquakes occur quasi-periodically and that a mean recurrence time and its standard deviation can be estimated from the historical record of such events. Nishenko (1985) and Nishenko (1991) estimated the conditional probability for events filling the gap for 5 yr (1989-1994), 10 yr (1989-1999) and 20 year periods ) based on a lognormal distribution approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El concepto de potencial sísmico (McCann et al, 1979) fue introducido en la Sismología como una medida de la posibilidad de generar terremotos fuertes a mediano plazo en sectores de las fronteras entre las placas tectónicas grandes. El origen de estos trabajos se remonta a la hipótesis del ciclo sís-mico de Fedotov, pasando por los trabajos de Kelleher (1972); Kelleher et al (1973) y Kelleher y McCann (1976) en los cuales se delimitan sectores de la frontera entre placas que son propensos a generar terremotos fuertes.…”
Section: Aspectos Del Mapa Sismotectónico De Cubaunclassified